2014
DOI: 10.1016/j.techfore.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship culture, total factor productivity growth and technical progress: Patterns of convergence towards the technological frontier

Abstract: A firm's set of knowledge processes may be affected by the entrepreneurial culture of the country in which it is located. Total factor productivity, mainly associated with technical progress, accounts for most differences over time and across countries. In the present work we examine the determinants of total factor productivity growth in 26 OECD countries between 1965 and 2010, breaking them down into changes in technical efficiency and shifts in technology over time. Using the U.S. as the technology frontier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…Authors such as Minniti and Lévesque (2010) and Colino et al (2014), among others, have used this idea to include entrepreneurship into the growth model. They develop a mathematical framework to demonstrate how entrepreneurship could lead to long-term equilibrium.…”
Section: Opportunity Entrepreneurship As An Endogenous Factor In Econmentioning
confidence: 99%
“…Authors such as Minniti and Lévesque (2010) and Colino et al (2014), among others, have used this idea to include entrepreneurship into the growth model. They develop a mathematical framework to demonstrate how entrepreneurship could lead to long-term equilibrium.…”
Section: Opportunity Entrepreneurship As An Endogenous Factor In Econmentioning
confidence: 99%
“…They found that more skilled labor generates positive externalities as well as more economic growth. Acs et al (2011), Blanchflower (2000, Colino et al (2014), Iyigun and Owen (1999) and Minniti and Lévesque (2010) used the neoclassical production function taking into account human capital as well as entrepreneurship (or self-employment) as special characteristics of individuals. Hence, entrepreneurship is assessed in an economic growth model to find its impact and complementarity.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars in entrepreneurship research have investigated the effects resulting from entrepreneurship (Wennekers and Thurik, 1999;Aparicio et al, 2016). Some argued that entrepreneurship brings social benefits as the intention of business creation is to generate: new jobs (van Praag and Versloot, 2007;van Stel et al, 2014), cluster formation (Rocha, 2004;Lee et al, 2012), technical change (Colino et al, 2014) and long-term economic growth (Fotopoulos, 2012;van Stel et al, 2014). Entrepreneurship is expected to lead to diversity, competition and knowledge learning, which ensure economic growth (Block et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Braunerhjelm et al (2010) showed that entrepreneurship Granger causes economic growth, based on Organisation for Economic Co-operation and Development (OECD) data from 1981-2002. Colino et al (2014) concluded that entrepreneurship is the most important driving force of economic growth. After analyzing data obtained from 26 OECD countries for the period 1965-2010, they found a strong positive correlation between entrepreneurship and TFP growth.…”
Section: Literature Reviewmentioning
confidence: 99%